EFFECT OF HEAT TREATMENT ON POTASSIUM CONTENT AND ANTI-SHIGELLOSIS ACTIVITY OF KLUTUK BANANAS (MUSA BALBISIANA COLLA) FRUIT FLOUR - KUSUMA, SRI AGUNG FITRI; RAMDHANI, DANNI; SETIAFIANTI, EMMANUEL MELATI (International Journal of Applied Pharmaceutics, 2022)
Objective: to investigate the effect of heat treatment on the potassium content and anti-shigellosis action of klutuk banana fruit flour. Methods: The klutuk banana fruit slices were heat-treated using a validated oven under varied parameters of 30-50 °C for 15–40 h. Based on its minimum inhibitory concentration (MIC) value and the potassium analysis, the selected condition was then applied to the processing of bananas to produce stable flour. Atomic Absorption Spectrophotometry (AAS) was used to quantify the potassium concentration after the MIC value was calculated using the microbroth dilution method. Results: The best heat treat for the anti-shigellosis activity with a MIC of 3.125 mg/ml was at 50 °C for 20 h. The amount of potassium in the flour of klutuk banana fruit that had the best anti-dysentery activity was 0.3773 mg/ml or 9.76% of the total potassium content. But according to our research, the lower water content of banana flour caused by longer drying times and higher temperatures had no effect on the existence of antimicrobial metabolites. Conclusion: The potassium gain and anti-shigellosis action of klutuk banana fruit were thus significantly impacted by heat during the flour-processing stage.